2018
DOI: 10.1101/409722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape of stimulation-responsive chromatin across diverse human immune cells

Abstract: The immune system is controlled by a balanced interplay among specialized cell types transitioning between resting and stimulated states. Despite its importance, the regulatory landscape of this system has not yet been fully characterized. To address this gap, we collected ATAC-seq and RNA-seq data under resting and stimulated conditions for 25 immune cell types from peripheral blood of four healthy individuals, and seven cell types from three fetal thymus samples. We found that stimulation caused widespread c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Because CD4 + T cells dynamically migrate to and egress from tissues through circulation, cells isolated from PBMCs likely represent a functionally diverse population of cells reflective of the specific immunological state of an individual. This is supported by previous functional genomic analyses of activated primary CD4 + cells demonstrating marked heterogeneity within and variability between individuals in the chromatin and expression profiles that overlap signatures from multiple sorted populations including Th 1 s, Th 2 s, and Th 17 s (18,22,33).…”
Section: Heterogeneity Of Activated Cd4 + T Cellssupporting
confidence: 73%
See 1 more Smart Citation
“…Because CD4 + T cells dynamically migrate to and egress from tissues through circulation, cells isolated from PBMCs likely represent a functionally diverse population of cells reflective of the specific immunological state of an individual. This is supported by previous functional genomic analyses of activated primary CD4 + cells demonstrating marked heterogeneity within and variability between individuals in the chromatin and expression profiles that overlap signatures from multiple sorted populations including Th 1 s, Th 2 s, and Th 17 s (18,22,33).…”
Section: Heterogeneity Of Activated Cd4 + T Cellssupporting
confidence: 73%
“…While the functionalization of CD4 + T cells is predominantly determined by the polarization of naive T cells (T naive ), recent results have suggested a high degree of variation within and plasticity between canonical subtypes (17). Indeed, we (18,19) and others (20)(21)(22) have shown that human circulating CD4 + T cells are composed of a mixture of canonical and non-canonical populations with significant interindividual variability in both the proportion and gene expression of each population (18).…”
mentioning
confidence: 96%
“…1d). Cell types were annotated using three parallel approaches: 1) correlation between aggregated cluster expression profiles and bulk RNA expression profiles from reference populations 21 , 2) differential gene expression, and 3) known marker gene expression (Methods, Supplementary Fig. 2a-c).…”
Section: Resultsmentioning
confidence: 99%
“…Clusters were also confirmed by identifying differentially expressed marker genes for each cluster and comparing to known cell type marker genes. Finally, we downloaded bulk RNA-seq count data from sorted immune cell populations from Calderon, et al 21 and compared bulk gene expression to pseudo-bulk expression profiles from single cell clusters. UMI counts were summed for all cells in each cluster to generate pseudo-bulk profiles.…”
Section: Principal Component Analysis (Pca) and Umap Clusteringmentioning
confidence: 99%
See 1 more Smart Citation